The incidence, prevalence and mortality of granulomatosis with polyangiitis in the UK Clinical Practice Research Datalink - Pearce, Fiona A.; Grainge, Matthew J.; Lanyon, Peter C.; Watts, Richard A; Hubbard, Richard B. (Oxford University Press, 2016)
Objectives: To estimate the incidence, prevalence and mortality of Granulomatosis with polyangiitis (GPA) in the United Kingdom. Methods: We conducted a historical cohort study using data from the Clinical Practice Research Datalink and Hospital Episode Statistics (CPRD-HES). We calculated incidence rate ratios, adjusted for age, gender and ethnicity, using Poisson regression. Results: We identified 462 cases diagnosed between 1997 and 2013. Our overall estimate of incidence was 11.8 (95% CI 10.7-12.9)/million person-years. Incidence in children (aged <16 years) was 0.88 (95% CI 0.40-1.96), and adults 14.0 (95% CI 12.8-15.4). The incidence was lower in females (adjusted IRR 0.68; 95% CI 0.56-0.81) and highest in the 55-69 year age-group (adjusted IRR 9.5, 95% CI 6.9-13.0; reference group 0-39 years). Incidence was not significantly different in the Black / Minority Ethnic population compared to the white population (adjusted odds ratio 0.78, 95% CI 0.53-1.13, p=0.13). The prevalence in 2013 was 134.9 (121.3-149.6) /million. Mortality was 13.6% at 1-year, and higher in HES than CPRD-identified cases (Hazard ratio 3.16, 95% CI 2.19-4.56, p<0.001). Conclusions: By combining primary and secondary care datasets we have found the incidence and mortality of granulomatosis with polyangiitis to be higher than previously reported. We predict that at present each year in the UK there will be approximately 700 new cases of whom 95 will die within 12 months.